A Regenerative Approach to Canine Osteoarthritis Using Allogeneic, Adipose-Derived Mesenchymal Stem Cells. Safety Results of a Long-Term Follow-Up - Kriston-Pál, Éva; Haracska, Lajos; Cooper, Paul; Kiss-Tóth, Endre; Szukacsov, Valéria; Monostori, Éva (Frontiers in Veterinary Science, 2020)
Mesenchymal stem cells (MSC) are emerging as an effective therapeutic tool in treating canine osteoarthritis (OA). In this report, we focused on the questions of whether MSC transplantation has long-term beneficial effects for the improvement in motion and also evaluated the safety of MSC injection. Visceral adipose tissue, a surgical waste obtained during routine ovariectomy served as a source of allogeneic MSCs and used to treat OA. Altogether, fifty-eight dogs were transplanted in the study suffering from OA in the elbow (42 animals), hip (5), knee (8), ankle (2), and hock (1). The effect of MSC transplantation was evaluated by the degree of lameness at a 4-5-years follow-up period based on the owners' subjective observations. The results showed that 83% of the OA patients improved or retained improvement in lameness. Clinical safety of the treatment was assessed by evaluating the coincidence of tumors or other diseases and other adverse reactions (such as local inflammation) after MSC cell therapy. Two incidences of local inflammation for <1 week at the site of injection were reported. No other adverse reactions were detected post-treatment. Sixteen dogs died during the study, 4 due to cancer and 12 due to other diseases, diagnosed by veterinarians. Overall, our survey suggests that MSC transplantation has long-term beneficial effects in reducing lameness. Moreover, no enrichment in a specific cause of death was observed in the transplanted animals, compared to reported literature. Our data suggest that MSC treatment could be an effective and safe long-term therapy for canine OA.